Management and results of epilepsy surgery associated with acyclovir prophylaxis in four pediatric patients with drug-resistant epilepsy due to herpetic encephalitis and review of the literature. (November 2020) - Fohlen, Martine; Taussig, Delphine; Ferrand-Sorbets, Sarah; Maurey, Hélène; Petrescu, Anamaria; Chipaux, Mathilde; Delalande, Olivier; Dorfmuller, Georg
Abstract: Purpose: Herpes simplex virus encephalitis (HSE) is the most common cause of sporadic viral encephalitis in children and is responsible for epilepsy in approximately half of patients. In addition to medical treatment, epilepsy surgery may be offered to drug-resistant patients but carries a high risk of relapse of herpetic encephalitis. We are reporting our series of patients operated on between 2000 and 2019 with the systematic administration of acyclovir (ACV). Results: Four pediatric patients aged 4.5–12.8 years with drug-resistant epilepsy post-HSE underwent a tailored focal resection following invasive recordings (three patients) and a complete callosotomy (one patient). The total number of the surgical procedures for the four patients was eight, and a systematic administration of ACV as a prophylactic treatment of herpetic encephalitis relapse was done at each step. No patients had a relapse and the ACV was well-tolerated in all the cases. Following surgery two patients are seizure free, the patient who underwent callosotomy is Engel 3 and the fourth patient, in whom a large epileptic zone has contraindicated a second surgery, is Engel 4. Conclusions: Our series demonstrated the dramatic efficacy of systematic ACV prophylaxis during all cranial surgeries. Moreover, our results on epilepsy, together with those of the literature, encourage more consideration regarding epilepsy surgery in this specific etiology. All types of surgical procedures (curative or palliative) can be offered to the patients, but in the case of focal surgery, due to the poor anatomical limits, invasive recordings are highly recommended. Highlights: Acyclovir during cranial surgeries prevents relapse of herpetic encephalitis. Cranial surgery carries a high risk of relapse of herpetic encephalitis. Herpes virus encephalitis causes drug-resistant epilepsy in 50% of children. Surgery can be offered to children with post herpetic encephalitis epilepsy.